Towards an Australian Indigenous Women's Standpoint Theory - Moreton-Robinson, Aileen (Australian feminist studies, 2013)
In this article I outline an Australian Indigenous women's standpoint theory. I argue that an Indigenous women's standpoint generates problematics informed by our knowledges and experiences. Acknowledging that Indigenous women's individual experiences will differ due to intersecting oppressions produced under social, political, historical and material conditions that we share consciously or unconsciously. These conditions and the sets of complex relations that discursively constitute us in the everyday are also complicated by our respective cultural differences and the simultaneity of our compliance and resistance as Indigenous sovereign female subjects.
Keywords: approches et analyses; australie; cours; droits des femmes*; féminisme autochtone; histoire et politique; intersectionnalité; point de vue situé; pol4212; premier cycle; ressource en ligne; régions géographiques; thématiques